DEEP STRUCTURE OF THE EARTH'S CRUST IN THE DISTRICT OF THE SUKHOI LOG GOLD-PLATINUM DEPOSIT (EASTERN SIBERIA, RUSSIA) BASED ON GEOLOGICAL AND GEOPHYSICAL DATA - Lishnevskiǐ E.N.; Distler V.V. (My University, 2004)
The structure ofthe Earth's crust beneath the Sukhoi Log deposit is considered in the context of the deposit origin. A combination of geological, gravimetric, and geoelectric data helped us to distinguish three layers composing the Earth's crust beneth the deposit district: (1) an upper, shale-carbonate layer (R3-R2; 7-9 km thick) composing the Bodaibo synclinorium; (2) a middle, riftogenic layer (R1; 7-12 km thick) generally composed of basaltoids with ultramafic rocks, as well as Fe-rich metamorphic rocks (Fe-rich quartzites, magnetite ores, etc.); and (3) a lower layer (PR1-AR; 18-21 km thick) composed of strongly metamorphosed basic rocks, such as granulites. The analysis of geological, metallogenic, and geophysical data showed that the second and third layers could be the sources of ore components for the deposit. A 7- to 10-km uplift of activated mantle at a depth of 35-37 km is considered as the physical and energetic source of ascending heated deep fluids. As a result of the quantitative interpretation of the gravity field in the deposit district (on a scale of 1 : 200000) the Ugakhan granite pluton (cryptobatholith), located within the upper layer at a depth of 3 km, was distinguished. The pluton corresponds to a distinct local Ag minimum, The pluton is 6 km thick and has an area of 110 km2. The Sukhoi Log deposit is located 3 km above the roof of the peripheral part of the pluton. In contrast, granites are not recognized by gravimetric data beneath the smaller gold deposits of the Bodaibo synclinorium. We can conclude that the Paleozoic Ugakhan granite batholith, more than 600 km3 in volume, was the main factor in mobilization of ore components. The late magmatic and hydrothermal activity of this batholith controlled the gold and platinum migration and accumulation, which resulted in the formation of such a a large deposi as Sukhoi Log.